Strategi Kepemimpinan Partisipatif Kepala Sekolah dalam Perspektif Tabligh dan Fathonah - Ahmad Faoji; Raihany Bilqis (STIT Hidayatunnajah Bekasi, 2026)
The paradigm shift from authoritarian to participatory leadership in the Merdeka Belajar era requires school principals to be more inclusive. However, the integration of prophetic values in formal school management remains theoretically under-explored. This study aims to analyze how the traits of Tabligh (communication) and Fathonah (intelligence) can serve as a theoretical foundation for participatory leadership practices by school principals. This research employs a library research method with content analysis of educational management and Islamic leadership literature published between 2020-2025. The findings indicate that Tabligh manifests in vision transparency and information openness (communicative trust), while Fathonah serves as a strategic intelligence instrument for managing diverse opinions and wise decision-making. The synthesis of these two traits produces a prophetic-participatory leadership model that prioritizes not only democratic procedures but also moral integrity and intellectual quality. This study recommends empirical testing to observe the impact of this model on the school's work climate.